Insidious Flower Bug, Minute Pirate Bug Orius insidiosus Say (Insecta: Hemiptera: Anthocoridae) - Danielle Sprague; Joe Funderburk (EDIS)
This EDIS publication is an alternate version of a page published first on the Featured Creatures website. The Featured Creatures collection provides in-depth profiles of insects, nematodes, arachnids and other organisms relevant to Florida. These profiles are intended for the use of interested laypersons with some knowledge of biology as well as academic audiences. This 3-page fact sheet that discusses the insidious flower bug was written by Danielle Sprague and Joe Funderburk, and published by the UF Entomology and Nematology Department, October 2016.